KERAGAAN FREE SURFACE MODEL PALKA BERBENTUK KOTAK DAN SILINDER - Y. Novita; B. H. Iskandar; B. Murdiyanto; B. Wiryawan; Hariyanto Hariyanto (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2010)
Liquid cargo in the hold of life fish carier might influence ship stability. This is due to effect of free surface that is generated by liquid cargo movement during ship motion. This research exa-mined the effect of free surface from two kinds of hold that are formed into box and cylinder shapes.The result shows that, the effect of free surface of liquid cargo that placed in box shape hold givesless impact comparing to the one in cylinder shape.